1986
DOI: 10.2307/3430190
|View full text |Cite
|
Sign up to set email alerts
|

Fetotoxic Effects of Mono-2-Ethylhexyl Phthalate (MEHP) in Mice

Abstract: Mono(2-ethylhexyl) phthalate (MEHP), one of the main metabolites of di(2-ethylhexyl) phthalate (DEHP), exerted embryo/fetotoxic effects similar to those of DEHP at lower doses. Oral administration of MEHP (1 mL/kg) to the mice of 8 days gestation resulted in less than 32% of live fetuses, all of which were deformed.When DEHP (10 mL/kg) was given to the pregnant mice of 8 days gestation, approximately 0.03% and 0.003% of the administered dose was found in fetuses as DEHP and MEHP, respectively, after 12 hr.The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…To date, little information exists concerning transplacental crossing of these plasticizers in animal models [18,19], but DEHP-induced testicular damage and antiandrogenic action in prenatally exposed animals have been reported previously [6][7][8][9][10][11][12]. On the other hand, there is no indication concerning the distribution of phthalates in the maternal-placental-fetal compartments and DEHP/ MEHP-related toxicity of fetal exposure in humans.…”
Section: Discussionmentioning
confidence: 92%
“…To date, little information exists concerning transplacental crossing of these plasticizers in animal models [18,19], but DEHP-induced testicular damage and antiandrogenic action in prenatally exposed animals have been reported previously [6][7][8][9][10][11][12]. On the other hand, there is no indication concerning the distribution of phthalates in the maternal-placental-fetal compartments and DEHP/ MEHP-related toxicity of fetal exposure in humans.…”
Section: Discussionmentioning
confidence: 92%
“…Concerns arise, however, in special patient groups, like neonates, children, pregnant women, or patients with impaired liver function. DEHP can cross the placenta, 33 exposing the fetus secondarily to maternal exposures. Newborns and infants can receive the highest doses of DEHP from other medical interventions like extracorporeal membrane oxygenation or respiratory therapy 34 .…”
Section: Discussionmentioning
confidence: 99%
“…These effects are dose dependent, with a maximal no effect level of DEHP on mouse fetuses of 70 mg/kg/day. Tomita et al (1986) showed that effects of DEHP in mice depend on dose and timing of exposure. Exposure on gestational days 7 and 8 led to a high incidence of death and malformations, but exposure on other days had fewer effects (Tomita et al 1986).…”
Section: Reproductive and Developmental Toxicity In Animal Modelsmentioning
confidence: 99%
“…Tomita et al (1986) showed that effects of DEHP in mice depend on dose and timing of exposure. Exposure on gestational days 7 and 8 led to a high incidence of death and malformations, but exposure on other days had fewer effects (Tomita et al 1986). In utero exposure to DEHP causes embryotoxic and teratogenic effects in mice and rats (Shiota and Nishimura 1982;Tyl et al 1988).…”
Section: Reproductive and Developmental Toxicity In Animal Modelsmentioning
confidence: 99%